Simulations of gas flow in a Coal seam - Torbatynia, M.; Rasouli, Vamegh (APCBM, 2011)
Production of methane gas from coal seams is becoming very popular in the USA and also in Australia, as a natural source for clean gas. Coalbed methane (CBM) is classified as an unconventional reservoir, for which hydraulic fracturing is a commonly used stimulation technique to enhance production. A successful fracturing job is the one that provides maximum exposure to the natural fracture systems or cleats existing in the coal seam. The production from a coal seam depends highly on the permeability of both cleats and the coal itself. Drilling horizontal wells within the reservoir layer will increase the exposure of the formation with the wellbore wall and therefore it is a desired well trajectory to be used for CBM production. Depending on the stress regime a hydraulic fracture initiated in a vertical or a horizontal well could propagate longitudinally within the coal layer or transversely where the fracture develops in a plane nearly perpendicular to the coal seam plane. Also, fluid flow behaviour would be different depending on the production type, i.e. openhole or cemented liner with perforations. For example, in case of production from a cemented horizontal well with few perforations in place, the fluid may travel a shorter distance within the hydraulic fracture, but there would be a significant flow convergence around the perforation tunnels before the gas enters into the wellbore. In production from a transversely oriented fracture, however, the gas will travel a long distance within the fracture plane and will converge around a very small wellbore: a high fluid velocity is expected in this case.In this paper simple 2D simulations were carried out in order to investigate the change in production as a function of cleats and coal layer permeabilities. Also, the effects of cleat density and structures were studied. Change in flow behaviour as a result of horizontal drilling was investigated. Hydraulic fractures were considered in modelling and the results showed how gas flow will be improved by providing a larger exposure to the coal seam and intersecting larger number of cleats. Simulations were performed using ANSYS software. Designmodeler was used for model generation and FLUENT software was employed for flow analysis. The results indicate the capabilities of FLUENT for flow simulation purposes where different fluid properties as well as wellbore and perforation geometries could be considered.